Three‐Dimensional Fourier Analysis of Atmospheric Gravity Waves and Medium‐Scale Traveling Ionospheric Disturbances Observed in Airglow Images in Hawaii Over Three Years. Issue 10 (29th September 2022) - Naito, Hideto; Shiokawa, Kazuo; Otsuka, Yuichi; Fujinami, Hatsuki; Tsuboi, Takuma; Sakanoi, Takeshi; Saito, Akinori; Nakamura, Takuji
Abstract: Three‐dimensional Fourier spectral analysis of airglow images is a useful technique to provide propagation characteristics of atmospheric gravity waves (AGWs) in the mesopause region and medium‐scale traveling ionospheric disturbances (MSTIDs) in the thermosphere observed at emission wavelengths of 557.7 nm (altitudes: 90–100 km for AGWs) and 630.0 nm (200–300 km for MSTIDs). However, a statistical study of spectral analysis of airglow images over years has not been done yet at Hawaii. Here, we report the first spectral analysis of AGWs and MSTIDs using airglow images obtained at Haleakala (20.71°N, 203.74°E), Hawaii, during the three years from 2013 to 2016. The power spectral density (PSD) of AGWs tends to be larger toward north to northeast in summer and from north to west and southward in winter. The eastward (summer) and westward (winter) preferences are consistent with a wind‐filtering mechanism of AGWs by a mesospheric jet. Some correspondence is found between the locations of tropospheric convection activities and AGW propagation directions, suggesting that these mesospheric AGWs are originated from the troposphere. The PSDs of MSTIDs are larger in solstice than in equinox. This PSD enhancement in solstice is consistent with a sporadic‐E (Es) layer occurrence in either northern or southern hemisphere, suggesting that the MSTIDs over Hawaii could be caused by a coupling process between the Perkins and Es layer instabilities. A small correlation was found between the PSDs of AGWs in the mesopause region and the PSDs of MSTIDs, suggesting that the MSTIDs are partly caused by AGWs from the mesopause region. Plain Language Summary: Airglow images visualize atmospheric gravity waves (AGWs) in the mesopause region and medium‐scale traveling ionospheric disturbances (MSTIDs) in the thermosphere through the airglow emissions at wavelengths of 557.7 nm (emission altitudes: 90–100 km for AGWs) and 630.0 nm (200–300 km for MSTIDs). Hawaii is unique islands, which are isolated from any continent and located at middle‐subtropical latitudes. However, a spectral analysis of airglow images has not been done yet over Hawaii. Here, we report the first spectral analysis of AGWs and MSTIDs using airglow images obtained at Hawaii for 2013–2016. The AGWs tend to propagate toward north to northeast in summer and from north to west and south in winter. The characteristics of eastward (summer) and westward (winter) are consistent with the wind filtering of AGWs by a mesospheric jet. A weak correlation is found between tropospheric convection and the AGW amplitudes in winter, suggesting that these winter AGWs partly originate from the troposphere. The amplitude of MSTIDs is larger in solstice than in equinox. A small correlation was found for amplitudes of AGWs in the mesopause region and MSTIDs in the thermosphere, suggesting that the MSTIDs over Hawaii are partly caused by AGWs from the mesopause region. Key Points: We report the first Fourier spectral analysis of airglow images over Hawaii for emission wavelengths of 557.7 and 630.0 nm Propagation characteristics of mesospheric gravity waves and medium‐scale traveling ionospheric disturbances (MSTIDs) are shown MSTIDs are likely to be caused by ionospheric instabilities and atmospheric gravity waves over Hawaii